Synthesis and Kinematic Analysis for Bi-objective Path of Six-bar Linkage - Guangzhen Cui; Yanqiu Xiao; Caidong Wang; Zhiqiang Guo (Jixie chuandong)
Six-bar linkages have a wide range application in industry and daily life. To ensure the design accuracy and improve design efficiency，an integrated design method of synthesis and analysis for bi-objective path of six-bar linkages is put forward. Firstly，based on the set of nonlinear equations of bi-objective path for six-bar linkage，five general precision points is the largest number that can be achieved precision bi-objective path of six-bar linkage. Then，the regeneration homotopy algorithm is used to reach the fast solution of the synthesis equations，this algorithm is easy and does not involve the complex elimination process and the problem of selecting the initial value. In order to screen out the mechanism with practical engineering application value in the synthesized mechanism，the motion defect determination of six-bar mechanism is carried out based on the 2R Assur group cross product coincidence，the kinematics analysis of the loop equation of the six-bar mechanism is established. Finally，the example of opening-closing linkage for patient rehabilitation transfer device verifies the correctness and effectiveness of the proposed theory and methodologies.